Profil klinis wanita dengan sindrom ovarium polikistik - Erna Yovi Kurniawati; Soeharyo Hadisaputro; Agus Suwandono (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: The prevalence of polycystic ovary syndrome with insulin resistance in Indonesia in 2014 was 4,034,635 women (50-75%). More than two-thirds (69%) of women aged 18-40 years are overweight or obese, and women with PCOS who are overweight or obese constitute a large group at risk for cardiometabolic and psychological disorders. Objective: To determine the clinical profile and nutritional status of women with Down syndrome. polycystic ovaries. Methods: This study is a descriptive study with a cross-sectional design, conducted to analyze 30 women with Polycystic Ovary Syndrome.Results: Most PCOS symptoms are experienced by women with obesity II nutritional status, experiencing symptoms of irregular menstruation, acne, acanthosis nigricans, alopecia, fatigue, sleep apnea, hirsutism, and infertility compared to respondents who are obese I and overweight. Conclusion: Nutritional status is one of the factors that influence the occurrence of Polycystic Ovary Syndrome